The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/ejlt.201800329
|View full text |Cite
|
Sign up to set email alerts
|

Quality Parameters of Mechanically Extracted Edible Macauba Oils (Acrocomia aculeata) for Potential Food and Alternative Industrial Feedstock Application

Abstract: There is a need for knowledge on new sources of vegetable oils. Acrocomia aculeata is regarded as a promising alternative source to meet food and industrial demands. With a similar productive potential to Elaeis guineensis, this crop is among the highest oil‐yielding plants in the world. The present study characterizes the A. aculeata oil comprehensively to aid the setting up of standards encompassing the quality, composition, and identity. Samples are obtained under five different pressing conditions and scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 55 publications
2
13
1
4
Order By: Relevance
“…The composition of the oil extracted from fruit pulps in ''La Palma'' exhibited completely different characteristics, with higher content of oleic acid (76.4%) and lower content of palmitic acid (14%). In general, the fatty acid profiles of the samples taken from Costa Rican A. aculeata were similar to those reported for Brazilian accessions, where oleic acid was also the main component (between 55 and 60%), followed by palmitic acid (between 19 and 23%) and linoleic acid (between 4 and 10%) (Coimbra and Jorge 2012;Nunes et al 2015;Del Río et al 2016;Prates-Valério et al 2019). For E. guineensis accessions, oleic acid contributed 36% and palmitic acid 39% to the total pulp fatty acids (Prates-Valério et al 2019).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The composition of the oil extracted from fruit pulps in ''La Palma'' exhibited completely different characteristics, with higher content of oleic acid (76.4%) and lower content of palmitic acid (14%). In general, the fatty acid profiles of the samples taken from Costa Rican A. aculeata were similar to those reported for Brazilian accessions, where oleic acid was also the main component (between 55 and 60%), followed by palmitic acid (between 19 and 23%) and linoleic acid (between 4 and 10%) (Coimbra and Jorge 2012;Nunes et al 2015;Del Río et al 2016;Prates-Valério et al 2019). For E. guineensis accessions, oleic acid contributed 36% and palmitic acid 39% to the total pulp fatty acids (Prates-Valério et al 2019).…”
Section: Discussionsupporting
confidence: 79%
“…Industrial extraction of oil from A. aculeata fruits will result in the production of byproducts mainly from the husk fraction (Colombo et al 2018;Prates-Valério et al 2019). To extend the efficiency of the energy generation process and increase profits, it is advisable to exploit potential byproducts that can provide an added value, for example through use in the production of combustion-derived energy, carbon and activated charcoal (Evaristo et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In literature, were found works for the extraction of MKO using ultrasonic assisted extraction (Rosa et al, 2019), Soxhlet extractor (Alves, Argandoña, Linzmeier, Cardoso, & Macedo, 2016;Dário et al, 2018;Lescano et al, 2015;Lieb et al, 2019;Oliveira et al, 2017;Rosa et al, 2019), pressurized fluids (Trentini et al, 2019), and pressing (César et al, 2015;Río et al, 2016). The same techniques were used to obtain the MPO (César et al, 2015;Dário et al, 2018;Lescano et al, 2015;Río et al, 2016;Rodrigues et al, 2017;Trentini et al, 2019;Valério-Prates, Celayeta, & Cren, 2019). However, no studies were found on obtaining the oil from a mixture of kernel and pulp.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Acrocomia aculeata (known as macauba or bocaiuva) is a promising tropical palm for the production of vegetable oil for both the food and nonfood sectors (Prates-Valério et al, 2019). It grows in dry areas from Mexico and the Caribbean Islands to northern Argentina.…”
Section: Introductionmentioning
confidence: 99%